Patient Satifaction with Telepharmacy Services: Bibliometric Analysis - Dasopang, Eva Sartika; Hasibuan, Emilia; Syarah, Siti (Universitas Padjadjaran, 2025)
Telepharmacy, the remote delivery of pharmaceutical services using information and communication technologies, is an increasingly popular trend in healthcare and has great potential to improve patient satisfaction and access to healthcare. The use of bibliometric analysis can provide a more comprehensive understanding of research developments in this area. This study used bibliometric analysis of international publications using the keywords telepharmacy AND patient satisfaction from 2016 to 2023 using data sources from Scopus and further visual analysis using VOSviewer. Fifty-two suitable documents were obtained from 207 documents received. The keyword-related searches yielded 10 articles each in 2021 and 2023, and showed an increasing trend of publications related to telepharmacy and patient satisfaction, especially in 2022 (19 articles). The results also showed the existence of three main clusters related to telepharmacy, namely patient satisfaction, pharmacy and pharmacy services. This study shows that telepharmacy has emerged as an important area of research, especially during the COVID-19 pandemic. Telepharmacy has the potential to improve patient access to pharmaceutical services, increase patient satisfaction and improve the overall quality of healthcare.